Efforts to Increase Creativity and Achievement Learning Science through Empowerment Student Reasoning - Jailani Jailani; Almukarramah Almukarramah; Abubakar Abubakar; Ibrahim Ibrahim; M. Ridhwan; Anwar Anwar; Muhammad Usman; Lukmanulhakim Lukmanulhakim (BIRCU, 2022)
One of the main goals of science education is to encourage the intellectual development of students. In this case, what is to be achieved is that most students can develop their potential at the level of formal reasoning. In general, in today's science learning, reasoning has not been managed optimally, planned, and systematically. The low ability of students to solve problems and the level of reasoning affects their low learning achievement. One of the reasons is that so far students are more required to develop low-level thinking patterns. Preparation of a quality generation should be done through empowering students through problem solving by improving reasoning in any approach, strategy, method or technical effort of learning. Scientific reasoning is one of the factors that affect student achievement in science. Scientific reasoning also contributes to academic achievement, cognitive abilities, decision making, and problem solving. Scientific reasoning can be used as a foundation in understanding and doing science as well as an integral part of problem solving.